1971
DOI: 10.1627/jpi1959.13.189
|View full text |Cite
|
Sign up to set email alerts
|

Bond Nature of Peroxides and Related Compounds

Abstract: Summary:Extended Huckel molecular orbital calculations were performed on various peroxides (hydroperoxides, peracids, and peresters), nitrites, nitrates, esters, ethers, and alcohols with particular reference to the bond nature of their O-O, O-N, C-O, and O-H linkages. We made several findings. Firstly, the order of the bond strengths of the above linkages in the compounds considered was: alcohol>ester>ether>>nitrate>nitrite>>hydroperoxide>peroxide>perester> peracid. Secondly, peroxide families or nitrite and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1978
1978
1978
1978

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…Experiments using BP labelled with l8 O in the carbonyl group have shown that attack by trialkylstannyl and triphenylmethyl radicals also takes place at the peroxy-oxygen 120 . Quantum-chemical calculations, indicating a deficiency of electron density in the peroxylinkage, are consistent with this finding 175 . The weak influence of the polarity of the medium and the low reaction constants p in the Hammett and Taft equations may indicate the formation of a weakly polar transition state in this reaction, i.e.…”
Section: Reactions Of Verdazyls With Peroxy-compoundssupporting
confidence: 70%
“…Experiments using BP labelled with l8 O in the carbonyl group have shown that attack by trialkylstannyl and triphenylmethyl radicals also takes place at the peroxy-oxygen 120 . Quantum-chemical calculations, indicating a deficiency of electron density in the peroxylinkage, are consistent with this finding 175 . The weak influence of the polarity of the medium and the low reaction constants p in the Hammett and Taft equations may indicate the formation of a weakly polar transition state in this reaction, i.e.…”
Section: Reactions Of Verdazyls With Peroxy-compoundssupporting
confidence: 70%